Case 3704: Lepisma Linnaeus, 1758 (Insecta, Zygentoma, Lepismatidae): proposed reversal of Direction 71 (1957) regarding the gender of the name - Molero-Baltanás, Rafael; Smith, Graeme B; Mendes, Luis F; Gaju-Ricart, Miquel; Bach de Roca, Carmen (Bulletin of Zoological Nomenclature, 2016)
The purpose of this application, under Articles 78.1, 78.2.3 and 80.2 of the Code, is to resolve an ongoing issue involving the gender of the name of the silverfish genus Lepisma Linnaeus, 1758 and other generic names derived from Lepisma. Under Direction 71 issued by the Commission in 1957, Lepisma is deemed to be of feminine gender despite being etymologically neuter. Unfortunately, Direction 71 did not explicitly advise on the treatment of genus-group names derived from Lepisma, all of which are neuter under Article 30.1.2 of the Code but nonetheless have generally been treated as feminine. Under Article 29.5 of the Code, prevailing use of the family name Lepismatidae so spelled is not affected by the generic-level gender problem, but the scope of the gender-related confusion extends to almost half of the generic and specific names in the family Lepismatidae Latreille, 1802, including such cosmopolitan peridomestic pests as Lepisma saccharina Linnaeus, 1758 and Ctenolepisma longicaudata Escherich, 1905. Three possible resolutions are proposed: that the Commission confirm that Direction 71 stands and the gender of Lepisma is feminine and also either (1) confirm that under Article 30.1.2 of the Code all generic names derived from Lepisma are of neuter gender,thereby filling the gap in Direction 71, or (2) rule under the plenary power that all generic names derived from Lepisma are of feminine gender, thereby endorsing current usage; or (3) that the Commission use their plenary power to rescind Direction 71 such that Lepisma assumes its etymologically correct neuter gender, while also confirming that under Article 30.1.2 of the Code all genera with names derived from Lepisma are of neuter, not feminine, gender. Reasons are given for preferring the third option, despite the resulting need to emend at least 129 species-group names in the genera involved.
Keywords: Nomenclature; taxonomy; gender; Insecta; Zygentoma; Thysanura; Lepismatidae; Afrolepisma; Anisolepisma; Asiolepisma; Burmalepisma; Cretalepisma; Ctenolepisma; Gopislepisma; Hemilepisma; Heterolepisma; Hyperlepisma; Lepisma; Leucolepisma; Mirolepisma; Nebkhalepisma; Neoasterolepisma; Ornatilepisma; Panlepisma; Protolepisma; Tricholepisma; Psammolepisma; Sabulepisma; Sceletolepisma; Swalepisma; Xenolepisma; saccharina; longicaudata; silverfish